Survivor in the cancer context: a concept analysis. (5th March 2015) - Hebdon, Megan; Foli, Karen; McComb, Sara
Abstract Aim The aim of this analysis was to define survivor in the cancer context. Background Cancer survivor has been used in the cancer lexicon, but may not represent the individuals it defines. Design This concept analysis was completed according to Walker and Avant's method. Data sources PubMed, PsychInfo, CINAHL, JSTOR, Google and medical and public health websites. Review methods Thirty sources from multiple disciplines, published between 1987–2013, were analysed for recurrent themes and conceptual meaning. Critical attributes, antecedents and consequences were extrapolated. Model, related and contrary cases were developed based on an amalgamation of clinical observations. Illegitimate, borderline and invented cases were excluded for this reason. Results Survivor in the cancer context is an individual with a history of malignancy, who has lived through a personalized challenge and has ongoing positive and negative consequences. Not all cancer survivors would identify themselves using the term survivor. Conclusions This contributes to the paradigm shift of cancer as a chronic disease as it establishes the unique nature of the cancer experience while highlighting the long‐term concerns related to this set of diseases. The Theory of Uncertainty in Illness provides a framework to understand the individualized nature of being a cancer survivor. Nursing research and practice should address the personal experiences of cancer survivors while still focusing on general survivorship needs.